Apheresis and intravenous immunoglobulins used in addition to conventional therapy to treat high-risk pregnant antiphospholipid antibody syndrome patients. A prospective study. (June 2016) - Ruffatti, Amelia; Favaro, Maria; Hoxha, Ariela; Zambon, Alessandra; Marson, Piero; Del Ross, Teresa; Calligaro, Antonia; Tonello, Marta; Nardelli, Giovanni B.
Highlights: Conventional treatments fail in about 20% of antiphospholipid syndrome pregnancies. Therapy for high-risk antiphospholipid syndrome pregnancies is not yet established. Apheresis plus intravenous immunoglobulins were evaluated as a second-line therapy. The combined therapy outlined here led to a high birth rate and no side-effects. Abstract: Pregnant women with triple antibody positive antiphospholipid syndrome (APS) who have had thrombosis or a history of early, severe pregnancy complications are generally considered at high risk of pregnancy loss. The objectives of this study were to investigate the efficacy and safety of a relatively new treatment protocol used in addition to conventional therapy in high-risk pregnant patients affected with primary APS. The study's two inclusion criteria were: (1) the presence of triple antiphospholipid positivity, (2) previous thrombosis and/or a history of one or more early, severe pregnancy complications. Eighteen pregnancies occurring between 2002 and 2015 in 14 APS patients, (mean age 34.8 ± 3.6 SD) were monitored. All 14 (100%) patients had triple antiphospholipid positivity. In addition, six of them (42.8%) had a history of thrombosis, four (28.6%) had one or more previous early and severe pregnancy complications, and four (30.8%) met both clinical study criteria. The study protocol included weekly plasmapheresis or immunoadsorption and fortnightly 1 g/kg intravenous immunoglobulins. Seventeen of the pregnancies (94.4%) produced live neonates, all born between the 26th and 37th weeks of gestation (mean 33.1 ± 3.5 SD). One female (5.5%), born prematurely at 24 weeks, died of sepsis a week after birth. There were two cases (11.1%) of severe pregnancy complications. No treatment side effects were registered. Given the high live birth rate and the safety associated to it, the study protocol described here could be taken into consideration by medical teams treating high-risk APS pregnant patients.